Unified Methodology for Estimating Efficiency of Traffic Calming Measures – Example of Estonia - Juri Ess; Dago Antov (The Baltic Journal of Road and Bridge Engineering)
Traffic calming is an integral part of contemporary traffic planning and traffic management being used for fulfilling different tasks such as reducing vehicle speed and traffic volume, and in final terms reducing number of accidents. Traffic calming measures are notstandardized internationally and have significant differences in geometric shape and layout in different countries, as well as in Estonia. At the same time impacts of different calming measures are unstudied well, and often the surveys are incomparable to each other. There are also no certain recommendation which measures should be implemented under different conditions. One of the reasons for that is lack of tested methodology for estimating the effectiveness of calming measures. This paper describes research that aimed at developing such a methodology and conducting a pilot study to test it. Effectiveness of traffic calming measures is estimated from the perspectives of vehicle speed and public acceptance. The new methodology assumes conducting an experiment. It allows comparing efficiency of two or more measures of the same type. The pilot study was conducted in Tallinn with a sample of 30 drivers. Results of this study proved that the new methodology is suitable for estimating effectiveness of traffic calming measures.